2015
DOI: 10.3329/bjp.v10i3.23486
|View full text |Cite
|
Sign up to set email alerts
|

<i>Nigella sativa</i> improves the carbon tetrachloride-induced lung damage in rats through repression of erk/akt pathway

Abstract: The objective of this study was to examine whether Nigella sativa plays a protective role against the damage in the lung by administering carbon tetrachloride (CCl4) to rats. Male Wistar albino (n=28, 8 weeks old) rats were divided into 4 groups: a) negative control: Normal water consuming group to which no CCl4 and N. sativa was administered; b) Positive control: Normal water consuming group to which no CCl4 was administered but N. sativa was administered; c) CCl4 Group: Normal water consuming and group to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This lends credence to the mechanistic schematic we have depicted in Figure 3; as is shown in that diagram, several components of BC act to inhibit COX1/COX2 activity, which is indeed necessary to produce PGE2. In yet another study, researchers discovered that levels of erk are decreased upon N. sativa treatment of damaged rat lungs [49]. The erk repression discussed here is supported by our mechanistic analysis, which has found that kaempferol, a component of N. sativa, inhibits ERK1/2 activity.…”
Section: Discussionsupporting
confidence: 79%
“…This lends credence to the mechanistic schematic we have depicted in Figure 3; as is shown in that diagram, several components of BC act to inhibit COX1/COX2 activity, which is indeed necessary to produce PGE2. In yet another study, researchers discovered that levels of erk are decreased upon N. sativa treatment of damaged rat lungs [49]. The erk repression discussed here is supported by our mechanistic analysis, which has found that kaempferol, a component of N. sativa, inhibits ERK1/2 activity.…”
Section: Discussionsupporting
confidence: 79%
“…They reported that the catalase activities of brain and liver tissues decreased in the D‐galactose group compared to the control group, but they found a meaningful increase of catalase enzyme activity in the EA + D‐gal group. Aslan, Boydak, Can, and Kuloglu (2015) investigated whether the consumption of Nigella sativa is a protecting role against CCl 4 ‐induced lung damage in rats. They concluded that the MDA amount interestingly decreased in black seed + CCl 4 group in comparison to the CCl 4 group.…”
Section: Discussionmentioning
confidence: 99%
“…1 These factors increase mortality rate and put the extra burden on the patient and thereby increasing the overall cost of the treatment. 2 Carbon tetrachloride (CCl 4 ), a synthetic halogenated and the highly lipid soluble molecule, is applied on various laboratory animal models to study the potential roles of an 4 but it also significantly affects the heart, 5 brain, 6 lung, 7 reproductive organs and most importantly in kidney. 8 The actual mechanism of CCl 4 in the kidney is yet not clear but it is described that the pathogenic pathway is depending onto free radical-mediated oxidative stress.…”
Section: Introductionmentioning
confidence: 99%